Diagnostic utility of ocular symptoms and vision for cytomegalovirus retinitis - Yingna Liu (2018)
© 2016 Liu et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Purpose: Cytomegalovirus (CMV) retinitis remains a leading cause of blindness in countries with a high burden of AIDS. Although dilated fundus examinations are recommended for those with CD4 counts below 100 cells/μL, in practice only those with poor vision and/or symptoms are routinely referred for screening. Therefore, the predictive value of this common practice should be assessed. Methods: This is a prospective cross-sectional study. Patients with known HIV and a CD4 count of less than 100 cells/μL attending an HIV clinic in Chiang Mai, Thailand completed a standardized questionnaire about visual symptoms and underwent visual acuity testing and dilated fundus examination. Participants without CMV retinitis were invited for repeated examinations every 3 months until their CD4 count exceeded 100 cells/μL. Patient-level statistical analyses were conducted to calculate diagnostic test characteristics, with bootstrapping to account for correlated data. Results: Of 103 study participants, 16 had CMV retinitis diagnosed at some point during the study. Participants with CMV retinitis were more likely to complain of visual symptoms compared to those without CMV retinitis (p = 0.01), including scotoma (p = 0.0002), itchy or watery eyes (p < 0.0001), and eye pain (p = 0.003); they were also more likely to have visual acuity worse than Counting Fingers (p = 0.0003). However, the absence of eye symptoms and the absence of poor vision did not strongly affect the probability that a patient did not have disease (negative likelihood ratio 0.56 and 0.76, respectively). Conclusions: Ocular symptoms and poor visual acuity were poor diagnostic indicators for the presence of CMV retinitis. Systematic screening of HIV patients with CD4 counts below 100 cells/μl should be carried out to detect disease at an early stage, when blindness can still be prevented.